2010
DOI: 10.1007/s11101-010-9179-8
|View full text |Cite
|
Sign up to set email alerts
|

Blockage of chloride channels and anion transporters with pesticidal natural products and their synthetic analogs

Abstract: Ligand-gated chloride channels mediate a variety of functions in excitable membranes of nerve and muscle in insects, and have a long history as targets for neurotoxic insecticides. Recent findings from our laboratory confirm that the natural product silphinenes and their semi-synthetic analogs share a mode of action with the established ligand-gated chloride channel antagonist, picrotoxinin. The silphinenes are non-selective, being roughly equipotent on insect and mammalian receptors, but also possess lethal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Manse-AT is a peptide that possesses multiple effects on diverse targets in vitro, including the stimulation of JH biosynthesis by adult female CA in lepidopteran insects and the inhibition of AIT across the larval midgut epithelium of M. sexta. Kataoka et al 9 demonstrated that the biologically active core of Manse-AT was the octapeptide Manse-AT (6)(7)(8)(9)(10)(11)(12)(13), because its effect on JH biosynthesis stimulation was similar to that of Manse-AT. On the midgut, Manse-AT (6-13) has less potency (defined as the IC 50 ) than the native peptide Manse-AT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Manse-AT is a peptide that possesses multiple effects on diverse targets in vitro, including the stimulation of JH biosynthesis by adult female CA in lepidopteran insects and the inhibition of AIT across the larval midgut epithelium of M. sexta. Kataoka et al 9 demonstrated that the biologically active core of Manse-AT was the octapeptide Manse-AT (6)(7)(8)(9)(10)(11)(12)(13), because its effect on JH biosynthesis stimulation was similar to that of Manse-AT. On the midgut, Manse-AT (6-13) has less potency (defined as the IC 50 ) than the native peptide Manse-AT.…”
Section: Discussionmentioning
confidence: 99%
“…Manse-AT (7-13), Manse-AT (8-13) and Manse-AT (9-13) at 1000 nM exhibited a maximum inhibition of AIT of 14.80 ± 1.27%, 9.39 ± 1.32% and 3.05 ± 0.88%, respectively, compared with 17.09 ± 1.73% for Manse-AT (6-13), the lead peptide. Manse-AT (10-13) and Manse-AT (11)(12)(13) were both no different from zero according to the t-test (data not shown). Thus, the tetrapeptide and tripeptide were completely inactive in this assay.…”
Section: Effects Of Manse-at and Analogues On Midgut Active Ion Transmentioning
confidence: 92%
See 2 more Smart Citations
“…The present study used established pharmacological probes, cell growth, and patch clamp techniques, to detect expression of targets in Sua1B cells, a cell line first isolated from neonate Anopheles gambiae larvae [6]. Screens focused mostly on compounds affecting VSCCs, since these are known to exist in Sua1B cells [7], and blockers of these channels are insecticidal [8]. Special attention was made to correlate ion channel effects with changes in cell growth.…”
Section: Introductionmentioning
confidence: 99%